Keutamaan Dan Kedudukan Menuntut Ilmu Dalam Islam (Majelis Taklim) - Al-Muthmainnah; Setiawan, Aan (El-FAKHRU, 2022)
Abstract In the 4.0 era which will lead towards the industrial session 5.0, the institutions and Islamic education experience significant progress. In everyday life, the issues often arise in the atmosphere of society whose background is not from an educator or instructor and is classified as a layman or lacks Islamic knowledge. In the midst of the emergence of broadcasts on social media, lecture content that can be accessed at any time only applies to the urban or suburban community level, while rural communities who have not been touched by internet access cannot enjoy this. Meanwhile, in the perspectives of  Islam, seeking religious knowledge (syar’i) is very important for the servant in order to distinguish which things are allowed and what are prohibited in islam. In this paper, the focus is on discussing the primacy of studying in Islam using a library research approach, namely by collecting data, literature, and reference books that are considered to be related to the themes discussed. The results of this study are the primacy and position of studying in islam based on the description of Hadist that have been agreed upon by the authenticity scholars both in matan and sanad are obligatory (highly recommended). Keywords: The primacy of science, source of science